Effect of Grading Fingerling Hybrid Catfish (♀ Channel Catfish × ♂ Blue Catfish) on Growth, Production, Feed Conversion, and Food Fish Size Distribution. (23rd April 2018) - Torrans, Les; Ott, Brian
Abstract: Hybrid catfish (♀ Channel Catfish Ictalurus punctatus  × ♂ Blue Catfish I. furcatus ) production ponds often produce a wide size range of fish, and payments to farmers may be reduced due to discounts for larger fish. In general, fish under 1 lb or over 4 lb may decrease the price paid to farmers, but this is highly dependent on individual processors. The present study was conducted to determine the effect of grading hybrid catfish fingerlings on the size distribution of harvested food fish. Three 0.25‐acre ponds were stocked with ungraded fingerlings (average weight = 0.05 lb; coefficient of variation [CV] = 78.0%) at 8, 000 fish/acre. An additional three 0.25‐acre ponds were stocked with double‐graded fingerlings of the same average weight (0.05 lb) as the ungraded fingerlings but with a significantly reduced size variation (CV = 26.9%). Grading of the fingerlings had no significant effect on any production variable other than final size variation (ungraded fingerlings: CV = 48.2%; graded fingerlings: CV = 26.1%). Final mean weights were identical (1.1 lb) and feed conversion ratios were nearly identical (1.58 and 1.57) between the treatments. Survival and net production were similar between treatments. Overall, 13.5% of ungraded fish and 1.2% of graded fish were less than 0.5 lb at harvest; 5.6% of the ungraded fish and 0.1% of the graded fish were larger than 2.0 lb. Grading of hybrid catfish fingerlings is an effective means of decreasing food fish size variability without impacting production efficiency.